Redes funcionais cerebrais de mulheres com fibromialgia : estudo transversal controlado - Pereira, Akeline Santos de Almeida (2022)
Introduction: Fibromyalgia (FM) is defined as a rheumatic syndrome, characterized by diffuse musculoskeletal pain for more than three months, associated with several clinical and psychoemotional symptoms, such as cognitive difficulties, anxiety, sleep disorders and depression. With etiology and pathophysiology still not understood, it is an underdiagnosed disease, because its diagnosis is made through history, questionnaires and clinical tests, not having an exam or biomarker that makes its diagnosis reliably. Technological advances have provided, through neuroscience, to build functional brain networks to improve the understanding of complex systems such as the human brain and, thus, understand the brain functioning of people with diseases such as FM. Objective: To investigate the brain dynamics of women with FM and women without chronic pain at rest and during cognitive activity. Material and Methods: This is a cross-sectional case-control study. Forty-five women participated, 25 with a clinical diagnosis of FM and 20 women without chronic pain. The members of both groups, fibromyalgia (GFM) and control (GCO) were evaluated through an evaluation form with sociodemographic data. Brain electrical activity (32-channel EEG) was also evaluated for 5 minutes with eyes closed and 5 minutes associated with the performance of cognitive activity, which consisted of individuals mentally counting high (rare) sounds amid low sounds (frequent). EEG data were filtered and artifacts removed automatically in MATLAB®'s EEGLAB program. Then, we used the method of synchronization by motifs to construct functional brain networks and produce indices to assess brain connectivity, cortical stability and intra and inter-hemispheric connections. In addition to the aforementioned assessments, common among the groups, the GFM was submitted to clinical assessments such as pain intensity; pressure pain threshold; temporal summation and conditioned pain modulation; and with questionnaires to assess the impact of fibromyalgia; perceived state of depression; anxiety; pain catastrophizing; quality of life and quality of sleep. Results: It was found that cortical connectivity decreased during cognitive stimulation compared to baseline in GFM (F=9.099; p=0.004) and GCO (F=5.634; p=0.022). When comparing the groups, it was observed that there was no difference in cortical connectivity at baseline (F=0.987; p=0.326; d=0.297); however, cortical connectivity during cognitive stimulation was found to be lower in the GFM compared to the GCO (F=19.262; p=0.001; d=1.304). There was an increase in homophily during cognitive stimulation in relation to baseline in the left hemisphere (F=7.477; p=0.008) and, in the right hemisphere, there was no significant difference (F=3.712; p=0.057). However, in the OCG, homophily increased during cognitive stimulation compared to baseline in the left (F=9.710; p=0.002) and right (F=10.081; p=0.002) hemispheres. It was noticed that the coefficient of variation of agglomeration (CVAg) increased during the cognitive stimulus compared to the baseline moment in the GFM (F= 15.958; p=0.001), whereas in the GCO (F= 0.358; p=0.553) they were not observed changes. There were no differences between GCO and GFM at baseline (F=0.530; p=0.471; d=0.218); however, it was observed that the CVAg was higher in the GFM compared to the OCG during the cognitive stimulus (F= 11.957; p=0.001; d= 1.072). Conclusions: Patients with FM showed reduced cortical connectivity, increased intra-hemispheric connections (homophilia) in the left hemisphere, and lower brain stability during cognitive stimulation.